Pregunta
upstudy study bank question image url

EXERCISE 7 Solve for \( x \) : \( \begin{array}{lll}\text { (a) } 3^{x}=1 & \text { (b) } 2^{x}=\sqrt{2} & \text { (c) } 4^{x}=8 \\ \text { (d) }\left(\frac{1}{9}\right)^{x}=27 & \text { (e) } 16 \cdot 16^{x}=64 & \text { (f) } 3^{x+1}=\frac{\sqrt{n}}{3} \\ \text { (g) } 4\left(\frac{1}{4}\right)^{x-1}=8 & \text { (h) } \frac{1}{3}(3)^{x-1}=\frac{1}{27} & \text { (i) } 8^{x} \cdot 16^{x-1} \\ \text { (i) } \frac{3^{2 x-1}}{3^{x}}=3 & \text { (k) } \sqrt[3]{9}=(\sqrt{3})^{2 x} & \text { (l) } \\ \text { (m) } 8^{-x}-2.4^{x-1}=0 & \text { (n) } 6^{x}+6^{x}+6^{x}+6^{x}+6^{x}+6^{x}=6^{6 x}\end{array} \)

Ask by Turnbull Mccoy. in South Africa
Jan 29,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

Here are the solutions for each part of the exercise: - (a) \( x = 0 \) - (b) \( x = -1 \) - (c) \( x = \frac{3}{2} \) - (d) \( x = -\frac{3}{2} \) - (e) \( x = \frac{1}{2} \) - (f) Cannot be solved without knowing \( n \) - (g) \( x = -\frac{1}{2} \) - (h) \( x = -1 \) - (i) \( x = \frac{4}{7} \) - (j) \( x = 2 \) - (k) \( x = \frac{1}{3} \) - (l) \( x = \frac{1}{5} \) - (m) \( x = \frac{1}{5} \)

Solución

Solve the equation by following steps: - step0: Solve for \(x\): \(3^{x}=1\) - step1: Rewrite in exponential form: \(3^{x}=3^{0}\) - step2: Set the exponents equal: \(x=0\) Solve the equation \( 2^{x}=\frac{1}{2} \). Solve the equation by following steps: - step0: Solve for \(x\): \(2^{x}=\frac{1}{2}\) - step1: Rewrite the expression: \(2^{x}=2^{-1}\) - step2: Set the exponents equal: \(x=-1\) Solve the equation \( 4^{x}=8 \). Solve the equation by following steps: - step0: Solve for \(x\): \(4^{x}=8\) - step1: Rewrite in exponential form: \(2^{2x}=2^{3}\) - step2: Set the exponents equal: \(2x=3\) - step3: Divide both sides: \(\frac{2x}{2}=\frac{3}{2}\) - step4: Divide the numbers: \(x=\frac{3}{2}\) Solve the equation \( \frac{1}{9^{x}}=27 \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{1}{9^{x}}=27\) - step1: Rearrange the terms: \(9^{-x}=27\) - step2: Rewrite in exponential form: \(3^{-2x}=3^{3}\) - step3: Set the exponents equal: \(-2x=3\) - step4: Change the signs: \(2x=-3\) - step5: Divide both sides: \(\frac{2x}{2}=\frac{-3}{2}\) - step6: Divide the numbers: \(x=-\frac{3}{2}\) Solve the equation \( \frac{3^{2x-1}}{3^{x}}=3 \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{3^{2x-1}}{3^{x}}=3\) - step1: Simplify: \(3^{x-1}=3\) - step2: Set the exponents equal: \(x-1=1\) - step3: Move the constant to the right side: \(x=1+1\) - step4: Add the numbers: \(x=2\) Solve the equation \( \frac{1}{3} \times 3^{x-1}=\frac{1}{27} \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{1}{3}\times 3^{x-1}=\frac{1}{27}\) - step1: Multiply the terms: \(3^{x-2}=\frac{1}{27}\) - step2: Rewrite in exponential form: \(3^{x-2}=3^{-3}\) - step3: Set the exponents equal: \(x-2=-3\) - step4: Move the constant to the right side: \(x=-3+2\) - step5: Add the numbers: \(x=-1\) Solve the equation \( 16 \times 16^{x}=64 \). Solve the equation by following steps: - step0: Solve for \(x\): \(16\times 16^{x}=64\) - step1: Multiply the terms: \(16^{x+1}=64\) - step2: Rewrite in exponential form: \(2^{4\left(x+1\right)}=2^{6}\) - step3: Set the exponents equal: \(4\left(x+1\right)=6\) - step4: Divide both sides: \(\frac{4\left(x+1\right)}{4}=\frac{6}{4}\) - step5: Divide the numbers: \(x+1=\frac{3}{2}\) - step6: Move the constant to the right side: \(x=\frac{3}{2}-1\) - step7: Subtract the numbers: \(x=\frac{1}{2}\) Solve the equation \( 8^{x} \times 16^{x-1}=1 \). Solve the equation by following steps: - step0: Solve for \(x\): \(8^{x}\times 16^{x-1}=1\) - step1: Multiply the terms: \(2^{7x-4}=1\) - step2: Rewrite in exponential form: \(2^{7x-4}=2^{0}\) - step3: Set the exponents equal: \(7x-4=0\) - step4: Move the constant to the right side: \(7x=0+4\) - step5: Remove 0: \(7x=4\) - step6: Divide both sides: \(\frac{7x}{7}=\frac{4}{7}\) - step7: Divide the numbers: \(x=\frac{4}{7}\) Solve the equation \( 6^{x}+6^{x}+6^{x}+6^{x}+6^{x}+6^{x}=6^{6x} \). Solve the equation by following steps: - step0: Solve for \(x\): \(6^{x}+6^{x}+6^{x}+6^{x}+6^{x}+6^{x}=6^{6x}\) - step1: Simplify: \(6^{x+1}=6^{6x}\) - step2: Set the exponents equal: \(x+1=6x\) - step3: Move the variable to the left side: \(x+1-6x=0\) - step4: Subtract the terms: \(-5x+1=0\) - step5: Move the constant to the right side: \(-5x=0-1\) - step6: Remove 0: \(-5x=-1\) - step7: Change the signs: \(5x=1\) - step8: Divide both sides: \(\frac{5x}{5}=\frac{1}{5}\) - step9: Divide the numbers: \(x=\frac{1}{5}\) Solve the equation \( 4 \times \frac{1}{4^{x-1}}=8 \). Solve the equation by following steps: - step0: Solve for \(x\): \(4\times \frac{1}{4^{x-1}}=8\) - step1: Simplify: \(4^{-x+2}=8\) - step2: Rewrite in exponential form: \(2^{2\left(-x+2\right)}=2^{3}\) - step3: Set the exponents equal: \(2\left(-x+2\right)=3\) - step4: Divide both sides: \(\frac{2\left(-x+2\right)}{2}=\frac{3}{2}\) - step5: Divide the numbers: \(-x+2=\frac{3}{2}\) - step6: Move the constant to the right side: \(-x=\frac{3}{2}-2\) - step7: Subtract the numbers: \(-x=-\frac{1}{2}\) - step8: Change the signs: \(x=\frac{1}{2}\) Solve the equation \( 8^{-x}-2 \times 4^{x-1}=0 \). Solve the equation by following steps: - step0: Solve for \(x\): \(8^{-x}-2\times 4^{x-1}=0\) - step1: Factor the expression: \(2^{-x}\left(1-2^{5x-1}\right)\times 4^{-x}=0\) - step2: Separate into possible cases: \(\begin{align}&2^{-x}=0\\&1-2^{5x-1}=0\\&4^{-x}=0\end{align}\) - step3: The statement is false for any value of \(x:\) \(\begin{align}&x \notin \mathbb{R}\\&x=\frac{1}{5}\\&x \notin \mathbb{R}\end{align}\) - step4: Find the union: \(x=\frac{1}{5}\) Here are the solutions for each part of the exercise: ### (a) \( 3^{x} = 1 \) To solve for \( x \): \[ x = 0 \] ### (b) \( 2^{x} = \sqrt{2} \) Rewriting \( \sqrt{2} \) as \( 2^{1/2} \): \[ x = -1 \] ### (c) \( 4^{x} = 8 \) Rewriting \( 8 \) as \( 2^{3} \) and \( 4 \) as \( 2^{2} \): \[ (2^{2})^{x} = 2^{3} \implies 2^{2x} = 2^{3} \implies 2x = 3 \implies x = \frac{3}{2} \] ### (d) \( \left(\frac{1}{9}\right)^{x} = 27 \) Rewriting \( \frac{1}{9} \) as \( 9^{-1} \) and \( 27 \) as \( 3^{3} \): \[ (3^{-2})^{x} = 3^{3} \implies 3^{-2x} = 3^{3} \implies -2x = 3 \implies x = -\frac{3}{2} \] ### (e) \( 16 \cdot 16^{x} = 64 \) Rewriting \( 64 \) as \( 16^{\frac{3}{2}} \): \[ 16^{1} \cdot 16^{x} = 16^{\frac{3}{2}} \implies 16^{x+1} = 16^{\frac{3}{2}} \implies x + 1 = \frac{3}{2} \implies x = \frac{1}{2} \] ### (f) \( 3^{x+1} = \frac{\sqrt{n}}{3} \) This equation cannot be solved without knowing the value of \( n \). ### (g) \( 4\left(\frac{1}{4}\right)^{x-1} = 8 \) Rewriting \( 8 \) as \( 4^{\frac{3}{2}} \): \[ 4 \cdot 4^{-(x-1)} = 4^{\frac{3}{2}} \implies 4^{1-(x-1)} = 4^{\frac{3}{2}} \implies 2 - x = \frac{3}{2} \implies x = -\frac{1}{2} \] ### (h) \( \frac{1}{3}(3)^{x-1} = \frac{1}{27} \) Rewriting \( \frac{1}{27} \) as \( 3^{-3} \): \[ \frac{1}{3} \cdot 3^{x-1} = 3^{-3} \implies 3^{x-1-1} = 3^{-3} \implies x - 2 = -3 \implies x = -1 \] ### (i) \( 8^{x} \cdot 16^{x-1} = 1 \) Rewriting \( 8 \) as \( 2^{3} \) and \( 16 \) as \( 2^{4} \): \[ (2^{3})^{x} \cdot (2^{4})^{x-1} = 1 \implies 2^{3x + 4(x-1)} = 1 \implies 3x + 4x - 4 = 0 \implies 7x = 4 \implies x = \frac{4}{7} \] ### (j) \( \frac{3^{2x-1}}{3^{x}} = 3 \) This simplifies to: \[ 3^{2x-1-x} = 3^{1} \implies 3^{x-1} = 3^{1} \implies x - 1 = 1 \implies x = 2 \] ### (k) \( \sqrt[3]{9} = (\sqrt{3})^{2x} \) Rewriting \( \sqrt[3]{9} \) as \( 3^{2/3} \): \[ 3^{2/3} = 3^{x} \implies \frac{2}{3} = 2x \implies x = \frac{1}{3} \] ### (l) \( 8^{-x} - 2 \cdot 4^{x-1} = 0 \) Rewriting \( 8 \) and \( 4 \): \[ (2^{3})^{-x} - 2 \cdot (2^{2})^{x-1} = 0 \implies 2^{-3x} - 2 \cdot 2^{2x-2} = 0 \implies 2^{-3x} - 2^{2x-1} = 0 \] This leads to: \[ -3x = 2x - 1 \implies -5x = -1 \implies x = \frac{1}{5} \] ### (m) \( 6^{x} + 6^{x} + 6^{x} + 6^{x} + 6^{x} + 6^{x} = 6^{6x} \) This simplifies to: \[ 6 \cdot 6^{x} = 6^{6x} \implies 6^{x+1} = 6^{6x} \implies x + 1 = 6x \implies 5x = 1 \implies x = \frac{1}{5} \] ### Summary of Solutions: - (a) \( x = 0 \) - (b) \( x = -1 \) - (c) \( x = \frac{3}{2} \) - (d) \( x = -\frac{3}{2} \) - (e) \( x = \frac{1}{2} \) - (f) Cannot be solved without \( n \) - (g) \( x = -\frac{1}{2} \) - (h) \( x = -1 \) - (i) \( x = \frac{4}{7} \) - (j) \( x = 2 \) - (k) \( x = \frac{1}{3} \) - (l) \( x = \frac{1}{5} \) - (m) \( x = \frac{1}{5} \)

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

Certainly! Let’s dive into solving these equations step by step! (a) To solve \(3^{x} = 1\), we recognize that \(1 = 3^0\). Therefore, \(x = 0\). (b) In \(2^{x} = \sqrt{2}\), we rewrite \(\sqrt{2}\) as \(2^{1/2}\). Thus, \(x = \frac{1}{2}\). (c) For \(4^{x} = 8\), we can express \(8\) as \(2^3\). Since \(4 = 2^2\), we have \(2^{2x} = 2^3\), leading to \(2x = 3\) and \(x = \frac{3}{2}\). (d) In \(\left(\frac{1}{9}\right)^{x} = 27\), we convert \(\frac{1}{9}\) to \(3^{-2}\) and \(27\) to \(3^3\). Thus, we have \(3^{-2x} = 3^3\), resulting in \(-2x = 3\) and \(x = -\frac{3}{2}\). (e) For \(16 \cdot 16^{x}=64\), we rewrite \(64\) as \(16^{3/2}\) (since \(64 = 4^3\) and \(4 = 16^{1/2}\)). This gives us \(16^{1 + x} = 16^{3/2}\), so \(1 + x = \frac{3}{2}\), leading to \(x = \frac{1}{2}\). (f) From \(3^{x+1} = \frac{\sqrt{n}}{3}\), we can express \(\frac{\sqrt{n}}{3}\) as \(3^{-1}n^{1/2}\) and simplify to \(3^{x+1} = n^{1/2} \cdot 3^{-1}\) which results in \(3^{x+2} = n^{1/2}\). (g) In the equation \(4\left(\frac{1}{4}\right)^{x-1} = 8\), simplifying gives \(4 \cdot 4^{-(x-1)} = 8\), or \(4^{2-x} = 8\) is equivalent to \(2^{4-2x} = 2^3\) leading us to \(4 - 2x = 3\), thus \(x = \frac{1}{2}\). (h) With \(\frac{1}{3}(3)^{x-1}=\frac{1}{27}\), we multiply both sides by 3, yielding \(3^{x-1} = \frac{1}{9} = 3^{-2}\). As a result, \(x-1 = -2\) which means \(x = -1\). (i) In \(8^{x} \cdot 16^{x-1}\), we can convert that into \(2^{3x} \cdot 2^{4(x-1)} = 2^{3x + 4(x-1)} = 2^{7x-4}\). (j) The equation \(\frac{3^{2x-1}}{3^{x}}=3\) simplifies to \(3^{x-1} = 3^1\), yielding \(x - 1 = 1\) hence \(x = 2\). (k) To solve \(\sqrt[3]{9}=(\sqrt{3})^{2x}\), we can write \(9\) as \(3^{2}\). So, \(3^{2/3} = 3^{x}\) gives \(x = \frac{2}{3}\). (l) In \(8^{-x}-2\cdot4^{x-1}=0\), first change \(4\) to \(2^2\) so this becomes \(2^{-3x} - 2\cdot2^{2(x-1)} = 0\). This can lead to a resolution by equating the exponents. (m) The equation \(6^{x}+6^{x}+6^{x}+6^{x}+6^{x}+6^{x}=6^{6x} \) combines terms yielding \(6 \cdot 6^{x} = 6^{6x}\), or \(6^{x+1}=6^{6x}\). So, \(x + 1 = 6x\) leading to \(x = \frac{1}{5}\). I

preguntas relacionadas

Latest Algebra Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad